Compound-specific carbon isotopic data for core and intact lipids in hydrothermally influenced Guaymas Basin sediments License:CC-BY: Creative Commons Attribution 4.0 International - Groninga, Janina; Lipp, Julius S; Song, Min; Hinrichs, Kai-Uwe (PANGAEA, 2025)
These datasets contain compound-specific stable carbon isotope values (δ¹³C, ‰ vs. VPDB) for a range of core lipids (CLs) and intact polar lipids (IPLs) of diverse microbial origin, derived from total lipid extracts (TLEs) of hydrothermally influenced marine sediments. The sediment cores utilized within this study were retrieved using the ALVIN submersible during the R/V Atlantis research cruises AT42-05 (Nov. 15-29, 2018) and AT37-06 (Dec. 09-27, 2016) targeting the southern Guaymas Basin spreading center (Core IDs: 4869-3, 4870-28, 4871-28; 4992-14 & 5000-9) and an off-axis Central Seep site on the northwestern flanks (Core ID: 4867-3). The δ¹³C value of trimethylsilyl-derivatized archaeol (AR) was measured using gas chromatography-isotope ratio mass spectrometry (GC-IRMS). In parallel, the TLEs were measured using reversed-phase ultra-high performance liquid chromatography/electrospray ionization/high-resolution mass spectrometry (UHPLC-ESI-HRMS), with the δ13C values of AR and a broad range of intact non-GC-amenable lipids calculated based on the M1/M0 ratio (first isotopologue over the monoisotopic peak) and corrected for the isotopic contributions of 2H, 15N, and 17O. This dataset was generated for the development of a new approach for compound-specific isotopic fingerprinting of non-GC-amenable lipids that enables the reliable identification of strongly 13C-depleted biomarkers indicative of microbial methane turnover in complex environmental samples.
Keywords: 13C composition; archaeol; Compound-specific carbon isotopes; Guaymas Basin; Intact polar lipids; stable carbon isotopes